(untitled) (Politeja, 2018)
In recent years, the Righteous Among the Nations have become a particular topic of interest for the official politics of memory, historians, NGO activists and the public sphere in Poland. Against the background of an on-going debate on Polish-Jewish relations during the Holocaust, the attitude of Polish society during the war and the commemoration of Holocaust sites in the country, the Righteous Among the Nations are presented as a positive aspect of this history of which many Poles are still proud. Thus, the topic has been frequently addressed by different actors and in different commemoration projects in recent years. This article aims to determine the various ways of how and with what aims the story of the Righteous has been used and defines three main directions: commemoration, education and justification (the latter in the sense of an attempt to cover up upcoming accusations of participation of Poles in the Holocaust). Another aspect covered will be the political use of the narrative of the Righteous in recent years, which will be shown on the basis of selected case studies. Based on the findings, the article investigates if and how the heritage of the Righteous is restricted to a national, patriotic context or goes further and comprises elements of what can be called a European set of values and contexts.